Melanocytic lesion evolution patterns with targeted therapies and immunotherapies for advanced metastatic melanoma: An observational study. (14th July 2017) - Zhao, Cathy Yunjia; Hwang, Shelley Ji Eun; Wakade, Deepal; Carlos, Giuliana; Anforth, Rachael; Fernández‐Peñas, Pablo
Abstract: Background/Objectives: Various cutaneous side‐effects have been reported with anti‐melanoma systemic therapies. This study investigated the changes in melanocytic lesion pigmentation in patients on four different therapies. Methods: We analysed the serial dermatoscopic photographs of atypical melanocytic lesions taken from patients with advanced metastatic melanoma on four different systemic therapies (selective BRAF‐inhibitor monotherapy, dabrafenib combined with trametinib [D&T], anti‐programmed cell death protein 1 [anti‐PD1] therapies, and anti‐PD1 combined with ipilimumab) seen from February 2013 to May 2016. We compared these changes with the melanocytic lesions of 10 control patients. Results: In the control group, 19% of naevi lightened, 64% did not change and 17% darkened. Only the BRAF inhibitor group showed more darkened lesions than controls (37%, P < 0.001). Meanwhile, there were more lightened naevi in the D&T therapy group (86%, P < 0.001) as well as the anti‐PD1 and ipilimumab groups (59%, P < 0.001) than controls. Patients on anti‐PD1 monotherapy had more lightened (49%) and fewer darkened naevi (9%) than controls, but differences were not significant. Conclusions: Our study showed that different anti‐melanoma systemic therapies have different effects on the pigmentation of melanocytic lesions. BRAF inhibitor may have the propensity to cause darkening while D&T therapy and anti‐PD1 caused lightening compared with controls. The findings emphasise the importance of regular dermatological monitoring in specialised clinics for patients on anti‐melanoma systemic therapy. Clinicians should expect changes in the global pigmentation of melanocytic lesions but be suspicious of lesions with structural changes.